1997
DOI: 10.1111/j.1538-4632.1997.tb00966.x
|View full text |Cite
|
Sign up to set email alerts
|

A Minimax Method for Finding the k Best “Differentiated” Paths

Abstract: lhis paper presents a new algorithm deterrnining the K-th best path without any circuit between two specified vertices in a connected, simple and nonoriented graph, The rnethod presented here is based on the well-known fact that the minimum set of ring sum of several Euler graphs and a special path between two vertices consists of all paths between the vertices. Lastly, an illu.strative example is giyen and the effLciency of the algorithn is estimated approxirnately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…In RSA-DSS, dissimilar routes are selected applying MinMax algorithm [26]. It is shown that Min-Max provides better capability in simultaneously considering length and dissimilarity of paths in comparison with other dissimilar routing algorithm.…”
Section: E Operational Problems In Rsa-dssmentioning
confidence: 99%
“…In RSA-DSS, dissimilar routes are selected applying MinMax algorithm [26]. It is shown that Min-Max provides better capability in simultaneously considering length and dissimilarity of paths in comparison with other dissimilar routing algorithm.…”
Section: E Operational Problems In Rsa-dssmentioning
confidence: 99%
“…Known effective methods for finding spatially dissimilar paths between two nodes in a transportation network include the Minimax method [34] and p-dispersion [35] but these heuristics suffer from a high computation cost which is undesirable for our setting where precomputation overhead for generating the K candidate routes must be kept small so that the system is able to register new continuous routing queries quickly.…”
Section: A K Candidate Pathsmentioning
confidence: 99%
“…While the underlying strategies for selection of the observed paths may not be known, comparison of the spatial forms of the paths may yield insights toward those strategies and behaviors. One approach to characterizing the spatial correspondence among paths is to determine the extent to which the arcs and nodes in both paths are shared or exactly correspond with one another (Huber ; Kuby, Zhongyi, and Xiaodong ; Akgun, Erkut, and Batta ). On one hand, two paths connecting a pair of nodes have an exact correspondence if they share the same ordered set of arcs and nodes.…”
Section: Introductionmentioning
confidence: 99%